Practical research - Leedy, Paul D. (Merrill Prentice Hall, 2001)
This book is divided into five parts: The Fundamentals; Focusing Your Research Efforts; Qualitative Research Methodologies; Quantitative Research Methodologies; and Preparing the Research Report.